Phytochemical Fingerprinting and In Vitro Antimicrobial and Antioxidant Activity of the Aerial Parts of Thymus marschallianus Willd. and Thymus seravschanicus Klokov Growing Widely in Southern Kazakhstan - Bagda Sagynaikyzy Zhumakanova; Izabela Korona-Głowniak; Krystyna Skalicka-Woźniak; Agnieszka Ludwiczuk; Tomasz Baj; Krzysztof Kamil Wojtanowski; Aleksandra Józefczyk; Karlygash Altynbekovna Zhaparkulova; Zuriyadda Bektemirova Sakipova; Anna Malm (Molecules, 2021)
The chemical composition of the hydroethanolic extracts (60% v/v) from the aerial parts of Thymus marschallianus Willd (TM) and Thymus seravschanicus Klokov (TS) from Southern Kazakhstan flora was analyzed together with their hexane fractions. Determination of antibacterial, antifungal and antioxidant activities of both extracts was also performed. RP-HPLC/PDA and HPLC/ESI-QTOF-MS showed that there were some differences between the composition of both extracts. The most characteristic components of TM were rosmarinic acid, protocatechuic acid, luteolin 7-O-glucoside, and apigenin 7-O-glucuronide, while protocatechuic acid, luteolin 7-O-glucoside, luteolin 7-O-glucuronide, and eriodictyol predominated in TS. The content of polyplenols was higher in TS than in TM. The GC-MS analysis of the volatile fraction of both examined extracts revealed the presence of thymol and carvacrol. Additionally, sesquiterpenoids, fatty acids, and their ethyl esters were found in TM, and fatty acid methyl esters in TS. The antioxidant activity of both extracts was similar. The antibacterial activity of TS extract was somewhat higher than TM, while antifungal activity was the same. TS extract was the most active against Helicobacter pylori ATCC 43504 with MIC (minimal inhibitory concentration) = 0.625 mg/mL, exerting a bactericidal effect. The obtained data provide novel information about the phytochemistry of both thyme species and suggest new potential application of TS as a source of bioactive compounds, especially with anti-H. pylori activity.